2023
DOI: 10.1038/s41398-023-02352-2
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol-specific transcriptional dynamics of memory reconsolidation and relapse

Abstract: Relapse, a critical issue in alcohol addiction, can be attenuated by disruption of alcohol-associated memories. Memories are thought to temporarily destabilize upon retrieval during the reconsolidation process. Here, we provide evidence for unique transcriptional dynamics underpinning alcohol memory reconsolidation. Using a mouse place-conditioning procedure, we show that alcohol-memory retrieval increases the mRNA expression of immediate-early genes in the dorsal hippocampus and medial prefrontal cortex, and … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(33 citation statements)
references
References 90 publications
(156 reference statements)
3
21
1
Order By: Relevance
“…Importantly, the increase in ERK1/2 activation was observed in the amygdala, but not in the mPFC and the NAc, which are also known as key regions for drug memory reconsolidation 17,33,44,56,62,[74][75][76] . These results are aligned with the findings of Barak et al that demonstrated increased activation of mTORC1, following retrieval of alcohol memories, using two different retrieval methods 17 .…”
Section: Erk1/2 Is Crucial For Alcohol Memory Reconsolidationmentioning
confidence: 95%
See 1 more Smart Citation
“…Importantly, the increase in ERK1/2 activation was observed in the amygdala, but not in the mPFC and the NAc, which are also known as key regions for drug memory reconsolidation 17,33,44,56,62,[74][75][76] . These results are aligned with the findings of Barak et al that demonstrated increased activation of mTORC1, following retrieval of alcohol memories, using two different retrieval methods 17 .…”
Section: Erk1/2 Is Crucial For Alcohol Memory Reconsolidationmentioning
confidence: 95%
“…Western blot procedure was conducted as previously described 62 . Briefly, immediately after dissection, brain tissues were homogenized in a radioimmunoprecipitation assay (RIPA) buffer containing:150 mM NaCl, 5 mM EDTA, 50 mM Tris HCl, 1% Triton X-100, 0.5% sodium deoxycholate, 0.1% sodium dodecyl sulfate (SDS) and protease and phosphatase inhibitors.…”
Section: Western Blotmentioning
confidence: 99%
“…Memory reconsolidation involves complex transcriptional and translational processes crucial for stabilizing memories [63][64][65] . For example, our recent RNA sequencing analysis in mice revealed transcriptional changes in the dorsal hippocampus and mPFC during contextual alcohol memory reconsolidation 15 . However, traditional bulk tissue analyses may be limited due to the small proportion of active neurons post drug-memory retrieval.…”
Section: A Unique Transcriptional Fingerprint Within Alcohol Memory N...mentioning
confidence: 99%
“…The neurobiological mechanisms of alcohol memory reconsolidation have been studied over the past decade. Several mesocorticolimbic regions have been implicated in the reconsolidation of alcohol memories, including the central amygdala (CeA) 3 , basolateral amygdala (BLA) 14 , dorsal hippocampus 15 and mPFC 3,10,15 . Interestingly, although the NAc plays an established role in addiction [16][17][18] , its role in alcohol memory processing and reconsolidation has only scarcely been described 19 .…”
Section: Introductionmentioning
confidence: 99%
“…It is well-established that the process of memory reconsolidation requires de-novo protein synthesis 20,23 , and it has been suggested that gene transcription is also required 24,25 . In line with the latter, using RNA sequencing, we recently characterized increases in the mRNA expression of a set of genes in the hippocampus and medial prefrontal cortex (mPFC) of mice following the retrieval of alcohol memories 25 . One of the genes exhibiting increased expression in the mPFC upon alcohol memory retrieval is Fkbp5 , which encodes for FK506 binding protein 51 (FKBP51), an important regulator of the hypothalamic-pituitary-adrenal (HPA) axis stress response system 26 .…”
Section: Introductionmentioning
confidence: 99%